Why am I doing this? Ambivalence in the context of Non-Suicidal Self-Injury - Gray, Nicole (Curtin University, 2023)
Why am I doing this? Ambivalence in the context of Non-Suicidal Self-Injury aimed to explore and understand experiences of ambivalence related to self-injury. Many factors are associated with varying levels of ambivalence related to self-injurious behaviour. It may be beneficial to recognise self-injury related ambivalence as a complex and confusing, yet natural component of decision making, in hopes to reduce confusion for the individual, improve client-clinician rapport, and enhance positive outcomes during treatment for self-injury.